Second Life and the Immersion Into Virtual Communities - Gonzalez Nuñez, Javier; Bolognesi, Manuel; Godbehear, Jane (IGI Global, 2024)
Enrapture, an innovative immersive tech development company based in Belgium, is one of the first businesses with a “virtual-world native” team that originally convened in Second Life a decade ago. Today, its strategic focus on user-generated content within virtual communities remains integral to its business strategy. Drawing from its extensive experience establishing leading ventures within Second Life, Enrapture facilitates seamless collaboration among virtual team members and expert partners across various time zones, aligning with the gig economy trend. This is characterized by flexible, contract-based work that challenges traditional employment paradigms. (Roy & Shrivastava, 2020). Central to the discourse on virtual immersion is the concept of the Metaverse—a sprawling landscape where virtual experiences converge with all social interactions and the commercial activities of a “creator economy” in a future version of the internet, the 3D internet. © The author © IGI Global.
Keywords: Second Life; Virtual Communities